Analisis peran guru dalam pembentukan karakter disiplin siswa kelas IV SD 02/II Senamat - Rahmadian Indriani; Tri Wera Agrita; Iri Hamzah (SAP (Susunan Artikel Pendidikan), 2025)
Observations of student behavior at SDN 02/II Senamat between February 10–11, 2025, served as the impetus for this study. According to observations, students typically showed up on time, dressed nicely, obeyed directions from professors, kept the classroom in order, and finished tasks on time. The study's goal was to explain how primary school teachers influence their kids' disciplined conduct. The study used a descriptive qualitative design. Among those who participated were 3 students, the school's principal, plus a homeroom teacher for the 4th grade. Miles and Huberman's interactive approach (data reduction, data display, and generating conclusions) was used to examine the data that were gathered through observation, interviews, and document review. Trustworthiness was strengthened through source triangulation, member checking, and an audit trail. Findings show that student discipline was reflected in six dimensions: obedience to rules, regularity in learning, consistency of behavior, responsibility, empathy, and diligence. Effective teacher strategies included modeling desired behavior, habituating positive routines, providing recognition and appropriate consequences, and offering consistent guidance. Supporting factors included family involvement, school culture, peer influence, community role models, and mindful use of media and technology. Obstacles included inconsistent student behavior, negative environmental influences, and weak media/technology control. The study highlights how important teachers are in helping students learn discipline, and it suggests working with families and the larger society to maintain character development.